2022
DOI: 10.1108/ijmf-04-2022-0177
|View full text |Cite
|
Sign up to set email alerts
|

Does economic policy uncertainty affect bank profitability?

Abstract: PurposeManagers are concerned about how the macroeconomic environment affects business profit. Focusing on banks, this study aims to investigate the effect of economic policy uncertainty (EPU) on bank profitability in 22 advanced countries.Design/methodology/approachThe study used the panel fixed effect regression methodology to assess the effect of EPU on several measures of bank profitability for 22 advanced countries from 1998 to 2017. The measures of bank profitability are net interest margin, lending-depo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 67 publications
1
17
1
Order By: Relevance
“…However, CBs provide customers with inflation-adjusted products, which adjusts with inflation and may be perceived to be better investment choices. This explanation is consistent with [ 14 ], who concluded that increases in economic policy uncertainty are associated on average with increases in bank profitability in Asia due to the distinct banking structure or regulation. Finally, Shariah supervisory boards (SSBs) may be a plausible explanation for the phenomenon because SSBs guide IBs and ensure compliance with Shariah principles, which can significantly back the credibility of IBs' products and influence customers' perception and confidence.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…However, CBs provide customers with inflation-adjusted products, which adjusts with inflation and may be perceived to be better investment choices. This explanation is consistent with [ 14 ], who concluded that increases in economic policy uncertainty are associated on average with increases in bank profitability in Asia due to the distinct banking structure or regulation. Finally, Shariah supervisory boards (SSBs) may be a plausible explanation for the phenomenon because SSBs guide IBs and ensure compliance with Shariah principles, which can significantly back the credibility of IBs' products and influence customers' perception and confidence.…”
Section: Resultssupporting
confidence: 91%
“…There are three major innovations of this work compared to extant research. First, recent literature has focused on the EU and stability nexus [ [10] , [11] , [12] ] as well as the performance or profitability nexus [ 13 , 14 ]. Other studies have examined the impact of EU on banks’ behaviour, such as lending behaviour [ 15 ], decreases in bank credit supply [ 16 ], and negative credit growth [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, most of the 120,000 below-the-line entertainment jobs lost were stage roles. The shutdown lost 150,000 members and 120,000 jobs, and the IATSE requested the government to include the entertainment industry in its stimulus package ( 56 ). From February 23 to March 1, 2020, the COVID-19 epidemic in Italy cost millions of euros every week.…”
Section: The Global Economy Hit By Coronavirus Pandemicmentioning
confidence: 99%
“…For the banking sector, ROE's examination is crucial due to banks' asset and income nature. The operational efficiency of the bank in generating profits, the efficient utilization of the bank's assets, and the level of equity are critical determinants of ROE [ [16] , [17] , [18] , [19] ]. According to ROE's theoretical definition, multiple studies have confirmed net profit's positive influence on ROE [ [20] , [21] , [22] ].…”
Section: Introductionmentioning
confidence: 99%
“…Our research contributes to existing literature in two main ways. Firstly, while there is extensive research employing ROE as a metric for evaluating financial performance and exploring its determinants at the firm level [ [16] , [17] , [18] , [19] ], the application of variables from the DuPont model to analyze ROE variabilities in Ugandan banks remains underexplored in the literature. In addition to the commonly utilized DuPont variables as ROE determinants, we integrate time-level variables as covariates into the hierarchical linear model (HLM).…”
Section: Introductionmentioning
confidence: 99%